Rethinking police procedural justice - Schaap Dorian; Saarikkomäki Elsa (SAGE PUBLICATIONS LTD, 2022)
While procedural justice theory has become the dominant paradigm in thinking about police legitimacy, it has several important weaknesses. First, procedural justice's conceptually essential distinction between 'process' and 'outcome' is blurred in reality, which is visible both in empirical operationalizations and in researchers' understanding of police work. Second, procedural justice theory views society through an implicit consensus lens, making it poorly equipped to address police-citizen conflicts and structural societal inequalities. This is evident in the theory's inability to unpack the dynamics of police-citizen interactions and its reluctance to problematize the police role in contemporary plural societies. To advance our understanding of police legitimacy and police-citizen relations, particularly among marginalized groups, we strongly recommend working toward theoretical renewal and empirical diversification.